Ordinance No. 317: An Ordinance Concerning Offenses and Disorderly Conduct, THE DAILY ASTORIAN, Feb. 22, 1879, at 3, § 7 (Astoria, OR) - (:unkn) unknown (General Publisher, 1879)
Any person or persons who shall draw any kind of fire arms, or any dirk, dagger, knife or other deadly weapon upon the person of another, or who shall strike at the person of another with slung-shot, knuckles or any other dangerous weapon, within the corporate limits of the city, shall on conviction thereof before the police judge be fined not less than five nor more than one hundred dollars or by imprisonment for not more than twenty days, or both.
--
Keywords: BRANDISHING